2021
DOI: 10.1055/s-0040-1722217
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Patients with Stroke

Abstract: Despite substantial advances in stroke care, vascular cognitive impairment remains a prominent source of disability. Unlike sensorimotor impairments, cognition often continues to decline after stroke. An aging population will increase the prevalence of vascular cognitive impairment, with stroke playing an important role. Ten percent of patients presenting with stroke have pre-stroke dementia; an additional 10% will develop incident dementia with a first stroke, and 30% with a recurrent stroke. While stroke inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 121 publications
(136 reference statements)
0
11
0
Order By: Relevance
“…Although, stroke is known to be a major contributor to both physical and cognitive decline, we cannot conclude with certainty that the differences in cognitive abilities between the stroke patients and the healthy controls were caused by the stroke per se ; the possibility that the stroke patients had a lower cognitive score even prior to the stroke must be taken into consideration. In fact, published data indicate that 10% of stroke patients have pre-stroke dementia [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although, stroke is known to be a major contributor to both physical and cognitive decline, we cannot conclude with certainty that the differences in cognitive abilities between the stroke patients and the healthy controls were caused by the stroke per se ; the possibility that the stroke patients had a lower cognitive score even prior to the stroke must be taken into consideration. In fact, published data indicate that 10% of stroke patients have pre-stroke dementia [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another risk factor for cognitive impairment in the elderly is ischemic or hemorrhagic stroke. According to studies, about 10% of patients with stroke had pre‐stroke dementia, 10% developed incident dementia following their first stroke, and 30% developed dementia with a recurrent stroke 9 . Cardiovascular metabolic risk factors (eg, diabetes, hypertension, hypercholesterolemia, obesity, metabolic syndrome, and vascular diseases) were associated with cognitive impairment and were independently associated with AD and VaD 10,11 .…”
Section: Risk Factors Of Geriatric Cognitive Impairmentmentioning
confidence: 99%
“…According to studies, about 10% of patients with stroke had pre-stroke dementia, 10% developed incident dementia following their first stroke, and 30% developed dementia with a recurrent stroke. 9 Cardiovascular metabolic risk factors (eg, diabetes, hypertension, hypercholesterolemia, obesity, metabolic syndrome, and vascular diseases) were associated with cognitive impairment and were independently associated with AD and VaD. 10,11 Studies showed that genetic risk factors play a significant role in both early-onset and late-onset AD, as well as other neurodegenerative diseases.…”
mentioning
confidence: 99%
“…The survivors of stroke have an increased risk of progressive cognitive impairment, even minor stroke ( 4 ). The presence of PSCI also affects the treatment of stroke patients in turn and nearly increases two-fold the risk of adverse outcomes ( 5 ). Lacunar infarction accounts for about 25% of stroke patients, and approximately half of the patients develop cognitive impairment in subsequent years ( 6 ).…”
Section: Introductionmentioning
confidence: 99%